Infamous 2 gets Sucker Punched. - Burt, Andy.
Sucker Punch Producer and Cofounder Brian Fleming discusses the birth of his studio, its influences, and the highly anticipated release of their superhero sandbox adventure, Infamous 2.
Keywords: Superheroes; Mardi Gras; Computer games; Sucker Punch; Infamous 2.